2002
DOI: 10.1159/000063025
|View full text |Cite
|
Sign up to set email alerts
|

Meiotic studies of male common shrews (<i>Sorex araneus</i> L.) from a hybrid zone between chromosome races

Abstract: Thirty-three adult male common shrews (Sorex araneus L.) were collected from a hybrid zone between two chromosomal races that differed in Robertsonian metacentrics. Anaphase I nondisjunction frequencies were estimated on the basis of metaphase II counts. RIV and CV complex heterozygotes (four-element rings and five-element chains at meiosis I, respectively) had substantially higher nondisjunction rates than homozygotes and simple Robertsonian heterozygotes. However, at least in the case of RIV-forming hybrids,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
24
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 18 publications
1
24
0
1
Order By: Relevance
“…3). This category of hybrids has been shown to be as fit as homozygotes in these shrews Fredga 1997, 1998;Banaszek et al 2002) and several backcross hybrids have been detected in this zone . In this situation, rearranged chromosomes can recombine independently and should form a much weaker linkage block than in HT.…”
Section: Differences Between Common and Rearranged Chromosomesmentioning
confidence: 79%
See 3 more Smart Citations
“…3). This category of hybrids has been shown to be as fit as homozygotes in these shrews Fredga 1997, 1998;Banaszek et al 2002) and several backcross hybrids have been detected in this zone . In this situation, rearranged chromosomes can recombine independently and should form a much weaker linkage block than in HT.…”
Section: Differences Between Common and Rearranged Chromosomesmentioning
confidence: 79%
“…Data from the S. araneus group suggest that Robertsonian heterozygotes do not suffer from infertility as substantially as other taxa (Searle 1993;Fredga 1997, 1998;Banaszek 2000). Nevertheless, Banaszek et al (2002) observed levels of nondisjunction high enough to affect fertility of complex heterozygotes. These authors highlighted the difference between simple and complex heterozygotes because they did not find any evidence that simple heterozygotes are less fit than homozygotes.…”
Section: Hybrid Dysfunction Versus Suppressed Recombination?mentioning
confidence: 95%
See 2 more Smart Citations
“…This hybrid zone occurs between Sorex antinorii, which is characterized by the metacentrics gi, hj, kn and l/o (notation: l/o, the slash indicating that the Robertsonian fusion is polymorphic), and the Vaud race of S. araneus, which is characterized by mg, hi, jl, kr and no, according to the nomenclature by Searle et al (1991) (Figure 1). F1 hybrids between these taxa should be relatively infertile because their chromosomes would assemble into a long chain of 11 elements during meiosis ('complex' heterozygotes, CXI; Figure 1) Fredga, 1997, 1998;Banaszek et al, 2002). To obtain balanced gametes (with a complete haploid set of chromosome arms) during meiosis, the species-specific chromosomes have to segregate in the same way as when they formed the F 1 zygote (Figure 1).…”
Section: Introductionmentioning
confidence: 99%